BREAKING SEED DORMANCY IN Sesbania punicea (Cav.) Benth - Grzeça, Gislaine Taís; Winhelmann, Mara Cíntia; Emer, Aquélis Armiliato; Tedesco, Marília; Lazarotto, Marília; Schafer, Gilmar (Scientia Agraria Paranaensis, 2021)
The objective of this study was to evaluate methods of breaking dormancy in Sesbania punicea seeds for seedling production. The treatments used were control, manual scarification for 40 s, manual scarification for 60 s, thermal scarification and chemical scarification. After the treatments were carried out, the seeds were placed to germinate at 25 ºC and a 16-hour photoperiod for 14 days. The germination percentage, average germination time, germination speed index, percentage of normal seedling formation, shoot length, root system length and percentage of hard seeds were evaluated. A completely randomized design with four replications of 25 seeds was used. The data were submitted to ANOVA and the means compared by Tukey 5%. There was a difference for all the analyzes evaluated, except for the length of the aerial part. The treatment with manual scarification 60 s had superior results, being indicated for overcoming dormancy of seeds of S. punicea.